METHOD OF DEVELOPMENT OF DACTILE AND SIGNED SPEECH IN "NATURAL" SCIENCE LESSONS - Zulfia Mamarajabova; Nazokat Abidova; Barno Subanova (The Bioscan, 2024)
The scientific and theoretical foundations of the development of dactylic and gestural speech of students with hearing impairments in classes on the subject "Natural Science" are analyzed. The content of the methodology for developing dactylic and gestural speech of students with hearing impairments in classes on the subject "Natural Science" is revealed.